2020
DOI: 10.1093/nar/gkaa847
|View full text |Cite
|
Sign up to set email alerts
|

Systematic use of synthetic 5′-UTR RNA structures to tune protein translation improves yield and quality of complex proteins in mammalian cell factories

Abstract: Predictably regulating protein expression levels to improve recombinant protein production has become an important tool, but is still rarely applied to engineer mammalian cells. We therefore sought to set-up an easy-to-implement toolbox to facilitate fast and reliable regulation of protein expression in mammalian cells by introducing defined RNA hairpins, termed ‘regulation elements (RgE)’, in the 5′-untranslated region (UTR) to impact translation efficiency. RgEs varying in thermodynamic stability, GC-content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…This finding is in contrast to the typical expectations for secondary structures in 5' UTRs to generally repress translation initiation. This finding is interesting because some synthetic small 5' UTR RNA hairpins have previously been found to improve protein expression 86 . In sum, our sequence selection strategy formalizes previously predicted rules for 5' UTR sequences that optimize ribosome load, and motivates an integrated approach to optimization of protein expression that jointly leverages our ribosome load dataset (Fig.…”
Section: Supplemental Text In-cell 5' Utr Sequence Selection To Determentioning
confidence: 91%
“…This finding is in contrast to the typical expectations for secondary structures in 5' UTRs to generally repress translation initiation. This finding is interesting because some synthetic small 5' UTR RNA hairpins have previously been found to improve protein expression 86 . In sum, our sequence selection strategy formalizes previously predicted rules for 5' UTR sequences that optimize ribosome load, and motivates an integrated approach to optimization of protein expression that jointly leverages our ribosome load dataset (Fig.…”
Section: Supplemental Text In-cell 5' Utr Sequence Selection To Determentioning
confidence: 91%
“…Gene sequence optimization can also adjust the GC content of genes, avoid base duplications, and eliminat restriction enzyme recognition sites, and also avoid similarity to important RNA motifs located in open reading frames that may interfere with mRNA processing and translational function, because they may cause ribosome pausing, in addition to factors such as CpG content and TATA boxes. Another 5′ untranslated region (5′ UTR) insertion into the RNA hairpin structure, the “regulatory element (RGE)”, also improves expression ( Eisenhut et al, 2020 ). In addition to gene sequence optimization, sequence motifs such as complementarity determining region three influences the rate of LC-HC dimerization during MAb synthesis, results in product-specific difference of yield ( Pybus et al, 2014 ).…”
Section: Genetic Modificationmentioning
confidence: 99%
“…The regulation of translation level and processing efficiency of translation products will also significantly affect the expression of target gene. Eisenhut et al developed the 5′-untranslated region (UTR) RNA-structures to impact translation efficiency, further systematically tune protein expression levels in mammalian cells and eventually help to optimize recombinant protein expression ( Eisenhut et al, 2020 ). Vivirius et al found a universal translation enhancer element in the 5′-end non-translation area of Hsp70 mRNA, which can enhance the translation efficiency of the cap-dependent structure ( Vivinus et al, 2001 ).…”
Section: Construction and Optimization Of Expression Vectorsmentioning
confidence: 99%